Upper Limb Home-Based Robotic Rehabilitation During COVID-19 Outbreak - Manjunatha, Hemanth; Pareek, Shrey; Jujjavarapu, Sri Sadhan; Ghobadi, Mostafa; Kesavadas, Thenkurussi; Esfahani, Ehsan T. (Frontiers in Robotics and AI, 2021)
The coronavirus disease (COVID-19) outbreak requires rapid reshaping of rehabilitation services. These services include the rehabilitation of patients recovering from severe COVID-19 with post-intensive care syndromes, including physical deconditioning and cognitive impairments, and other patients requiring physical therapy during the outbreak with no or limited access to hospital and rehabilitation centers. Considering the access barriers to quality rehabilitation settings and services imposed by social distancing and stay-at-home orders, these patients can be benefitted from providing access to affordable and good quality care through home-based rehabilitation. The success of such treatment will depend highly on the intensity of the therapy and effort invested by the patient. Monitoring patients' compliance and designing a home-based rehabilitation that can mentally engage them are the key elements in home-based therapy's success. Hence, in this paper, we first review the World Health Organization guidelines for rehabilitation during the current pandemic. We then study the state-of-the-art home-based upper limb robotic rehabilitation and provide suggestions on adapting the existing research frameworks to address the rehabilitation requirements for COVID-19. Finally, we suggest that the reformed rehabilitation services should consider both home-based solutions for enhancing the activities of daily living and an on-demand ambulatory rehabilitation unit for extensive training where we can monitor both cognitive and motor performance of the patients remotely.